UPAYA PENINGKATAN HASIL BELAJAR IPA MELALUI MODEL PEMBELAJARAN CTL SISWA KELAS III SEKOLAH DASAR - Megawati megawati; Sisca Oktavia (Jurnal Muara Pendidikan, 2020)
This research is motivated by the low quality of science learning, so that the impact on learning outcomes isn’t optimal. This study aims to describe the process of implementation and the achievement of science learning outcomes for each cycle of action through the application of the CTL model. This research is a classroom action research conducted at SDN 17/II Tanah Tumbuh with research subjects for all students in class III. The research instruments were teacher observation sheets, student observation sheets, and learning achievement test questions. This research was successfully carried out in 3 action cycles. Each cycle of action includes planning, implementing actions, observing, and reflecting activities. The results showed the percentage of the success of the teaching process of teachers in the first cycle reached 69%, in the second cycle increased by 70%, and in the third cycle successfully increased to 80%. The percentage of the success of student learning processes in the first cycle reached 74%, in the second cycle increased by 78%, and in the third cycle successfully increased to 85%. Student learning outcomes in the first cycle reached 67%, in the second cycle increased by 73%, and in the third cycle successfully increased to 87%. It can be concluded that the learning outcomes of science students can improve through the application of the CTL learning model.